Pemberdayaan Ekonomi Masyarakat Berbasis Lokal Di Desa Balongdowo Kecamatan Candi Kabupaten Sidoarjo - Oriza Satyva; Agustina, Isna Fitria (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2025)
The purpose of this study was to analyze and describe efforts to empower the community's economy through a local economic approach according to three main aspects of Hutomo's theory, namely resources, infrastructure, and capital. The research method applied is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The data analysis technique uses the Miles and Huberman model, including data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate findings, namely first, from the aspect of human and natural resources, MSME actors have promoted on social media to introduce MSME products and the village government helps MSME actors in administrative matters such as issuing business certificates. Second, from the aspect of facilities and infrastructure, MSME actors make processed products for out-of-town shipping and receive capital assistance from the cooperative office. Third, from the aspect of capital, MSME actors in building a business use personal capital supplemented by capital from external parties and marketing is carried out offline and online.